Enzymatic precipitation of cadmium by means of native bacteria of the genus Citrobacter. - Mogollón, L. I.; Rodríguez M., R.; Ramírez, N. E.; Zaucher, F. (CT&F - Ciencia, Tecnología y Futuro, 1997)
Native strains were isolated from heavy metal contaminated waters and soils. The microorganism selection was conducted based on the quantification of the phosphatase enzyme activity. Citrobacter cells in batch studies showed five times more enzymatic activity than that of available collection cultures and the reported values in previous studies using other strains. Uptake results show that cadmium removal increases with cell exposure time when the cell are in the presence of the enzymes substrate glycerol 2-phosphate. Metal enzyme affinity improves by increasing solution pH to 8-1 0. Precipitation is caused by passive bounding of cadmium to reactive groups at the cell wall and the "in situ" metal accumulation as nonsoluble phosphate on microbial cells wall.